Praise galore, but where are those courses? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Responding to Spore 87, a new reader, Ms A Nkebukwa of the Women s Research and Documentation Project at the University of Dar es Salaam in Tanzania, says she has been 'especially impressed by the brief, precise and interesting manner in which...